Do Acquirers Gain Real Wealth? : A Long Term Study in India - Limaye, Ketan C.; Pednekar, Achut P. (Indian Journal of Finance, 2017)
The present paper analyzed long term performance of M&A deals in India in terms of growth in shareholder value of acquirers in real terms and compared it with growth in nominal terms. It tried to understand whether M&A deals contribute to shareholder wealth of acquirers in real terms in comparison to nominal terms. We performed sectoral as well as overall analysis of a sample of 174 deals. We analyzed performance in three ways; in the form of growth of shareholder wealth of acquirers in nominal terms, growth of shareholder wealth of acquirers in real terms, and finally, a one on one comparison of performance in nominal terms vis a vis real terms. The study covered domestic M&A deals in India over a period of 1989 to 2014 involving Bombay Stock Exchange (BSE) listed acquirers. The model used for study is BHAR (Buy and Hold Abnormal Return) and a modification of BHAR, that is, RBHAR (Real Buy and Hold Abnormal Return). We did not find any significant difference between the test results of BHAR and RBHAR on a standalone basis. However, when we compared the performance of BHAR and RBHAR on a one to one basis, we found that the performance of M&A deals in auto and IT sectors in real terms was better than in nominal terms. Overall, M&A performance in real terms was also better than that in nominal terms.